Clinical and Pathological Aspects of Skin Diseases in Endocrine, Metabolic, Nutritional and Deposition Disease - Smoller, Bruce R.; Rongioletti, Franco; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Through a unique presentation of clinical photographs and accompanying histologic photomicrographs, Clinical and Pathological Aspects of Skin Diseases in Endocrine, Metabolic, Nutritional and Deposition Disease provides the practicing surgical pathologist, dermatologist, endocrinologist, internal medicine physician and dermatopathologist with a single volume source that reviews the clinical and pathologic features of metabolic and endocrine disorders that display cutaneous manifestations. Color photographs are presented for each condition followed by a series of phoromicrographs depicting each entity microscopically. The text includes Clinical Features, Pathology, Etiopathogenesis, Differential Diagnosis and Therapy for all entities, described in a clear, concise style. In-depth discussions of the clinical findings, as well as the histologic features of these diseases are included. Additionally, laboratory data used to make and support the diagnoses is discussed for each entity. The first section covers metabolic disorders that have cutaneous manifestations. Diseases organized by the endocrine organ primarily responsible for the systemic condition are covered. For each entity, an atlas of clinical manifestations is presented that will serve as a (3z(Bbed-side(3y (Bclinical reference, followed by a series of photomicrographs depicting the histologic changes. This unique format of presentation is followed throughout the volume in the second through fourth sections addressing Metabolic Diseases, Nutritional Disorders that affect the skin and finally Cutaneous Deposition Disorders. Clinical and Pathological Aspects of Skin Diseases in Endocrine, Metabolic, Nutritional and Deposition Disease is a unique reference for the practicing dermatopathologist, general pathologist reviewing skin biopsies, general dermatologists, internists and endocrinologists.s
Cutaneous Endocrine Disease -- Adrenal Disease -- Pancreas Disease and Diabetes Mellitus -- Thyroid Disease -- Pituitary Gland Diseases -- Parathyroid Disease -- Cutaneous Metabolic Disease -- Dyslipidemia (Hyperlipidemia) -- Gout -- Lipomatosis -- Obesity -- Porphyrias -- Hemochromatosis -- Metabolic Syndrome in Psoriasis -- Cutaneous Nutritional Disease -- Acquired Nutritional Deficiencies -- Anorexia Nervosa -- Alcohol Abuse -- Glucagonoma Syndrome and Necrolytic Migratory Erythema -- Cutaneous Deposition Disease -- Amyloidoses -- Mucinoses -- Lipoid Proteinosis -- Colloid Milium -- Calcification and Ossification -- Pigmentary Deposition Disorders -- Exogenous Cutaneous Deposits with Special Consideration to Skin Reactions to Soft-Tissue Fillers.
Keywords: Medicine; Dermatology; Internal medicine; Endocrinology; Metabolic diseases; Pathology; Medicine & Public Health; Pathology; Dermatology; Metabolic Diseases; Internal Medicine; Endocrinology